Layered materials for energy storage and conversion - Geng, Dongsheng; Cheng, Yuan; Zhang, Gang (Nanotechnologist) (RSC smart materials ;, 2019)
This book provides a comprehensive overview of recent and state-of-the-art research progress on layered materials for energy storage and other applications.